D6.8 - Report from the outreach activities - Hadjimitsis, Diofantos G.; Evagorou, Evagoras G.; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Themistocleous, Kyriacos; Papoutsa, Christiana; Mettas, Christodoulos; Lasaponara, Rosa; Masini, Nicola; Krauss, Thomas; Schreier, Gunter (My University, 2018)
The present deliverable is concentrated on the outreach activities that took place during the project for dissemination purposes. Social networks were used in order to maximize the publicity of the project and disseminate its results. The outreach activities were oriented towards a wider audience interested in innovative technologies and generally research innovation that was accomplished through these media sources.
Keywords: Outreach activities; ATHENA project